APHASIA IN THEORY OF EVERYTHING’S MOVIE - Tampubolon, Wahyu Alexander; Natsir, M.; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2019)
Theory of Everything’s Movie was analyzed in this study because it was based on a true story and also lots of lessons in life would be found in it. To support the analysis of the main character’s utterance in this movie, the writer used the theory of language disorder by Vasic. This study aimed to find the type of aphasia experienced by Stephen and how aphasia influence Stephen’s life. The method used by the writer is descriptive qualitative. The data of this study were analyzed by using Vasic’s theory about language disorder and the influence of aphasia by Windsor. In the process of analyzing all of those data, the writer had some procedures that include watching the movie several times, reading the movie script, then analyzing Stephen’s utterances related to aphasia. The result of this study showed that Broca’s aphasia and Wernicke’s aphasia occurred. Stephen has a brain injury in the left hemisphere. So, Stephen has a problem with his speech. Stephen was not able to speak clearly because of the disease, but his intelligence is still well. Aphasia changed Stephen’s life a lot. He cannot move as usual so that, he just sits on his electric wheelchair. Also, Aphasia makes people underestimate him. Aphasia makes Stephen difficult to speak so that, Stephen experienced communication disorder. The writer hoped that this research could help the next researcher to continue the analysis from the same movie with another theory of the linguistic case. The writer wished this research will enrich knowledge about language disorder especially aphasia. Film Theory of Everything dianalisis dalam penelitian ini karena didasarkan pada kisah nyata dan banyak pelajaran dalam kehidupan akan ditemukan di dalamnya. Untuk mendukung analisis ucapan karakter utama dalam film ini, penulis menggunakan teori gangguan bahasa oleh Vasic. Penelitian ini bertujuan untuk menemukan jenis afasia yang dialami oleh Stephen dan bagaimana afasia mempengaruhi kehidupan Stephen. Metode yang digunakan oleh penulis adalah deskriptif kualitatif. Data penelitian ini dianalisis dengan menggunakan teori Vasic tentang gangguan bahasa dan pengaruh afasia oleh Windsor. Dalam proses menganalisis semua data itu, penulis memiliki beberapa prosedur yang meliputi menonton film beberapa kali, membaca skrip film, kemudian menganalisis ucapan Stephen terkait dengan afasia. Hasil penelitian ini menunjukkan bahwa afasia broca dan afasia wernicke terjadi. Stephen mengalami cedera otak di belahan kiri. Jadi, Stephen punya masalah dengan pidatonya. Stephen tidak dapat berbicara dengan jelas karena penyakitnya, tetapi kecerdasannya masih baik. Aphasia banyak mengubah kehidupan Stephen. Dia tidak bisa bergerak seperti biasa sehingga, dia hanya duduk di kursi roda listriknya. Juga, Afasia membuat orang meremehkannya. Aphasia membuat Stephen sulit berbicara sehingga, Stephen mengalami gangguan komunikasi. Penulis berharap penelitian ini dapat membantu peneliti selanjutnya untuk melanjutkan analisis dari film yang sama dengan teori kasus linguistik lainnya. Penulis berharap penelitian ini akan memperkaya pengetahuan tentang gangguan bahasa terutama afasia